Manajemen Keberlanjutan Pertanian Kelapa di Desa Molanihu Kabupaten Gorontalo - Rahmita Nova; Amelia Murtisari; Irwan Bempah (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
Coconut plantations are one of the strategic commodities that play an important role in the national economy and community welfare. However, the development of coconut farming faces various obstacles, particularly the limited resources of farmers and difficulties in marketing. This study aims to 1) identify coconut farming management practices in Molanihu Village, Gorontalo, and 2) assess the sustainability of coconut farming in the area. A quantitative descriptive approach was used for the first objective, and the Multiaspect Sustainability Analysis (MSA) method was used for the second objective. The study involved 64 coconut farmers, selected through purposive sampling, utilizing both primary and secondary data. Three dimensions were analyzed: economic, social, and environmental. The results of the study indicate that coconut farming management has been implemented effectively, particularly in terms of group cooperation, harvesting systems, and labor utilization. However, improvements are needed in plant maintenance, market diversification, and the use of irrigation technology. The MSA analysis shows that the sustainability index of coconut farming is categorized as moderately sustainable. The social dimension (78.13) and environmental dimension (84.38) are classified as highly sustainable, while the economic dimension is still classified as moderately sustainable. The differences in indices between dimensions highlight the need for increased attention to enhance the overall sustainability of coconut farming.